Proposal of meta-requirement approach to analyze requirements specification completeness - Muhamad Idaham, Umar Ong; M. A., Ameedeen (2018)
Requirements validation plays an important role in ensuring the successfulness of a software development project. Requirements is the main necessity of a system. With the correct set of requirements, a correct and highly desired system should be able to be produced. But with the case of tender, requirements validation usually is not being invested by the development organization with the possibility of the tendered project will be assigned to a different vendor. The objectives of this research are to identify the major factors in validating user requirements, development of a reverse engineered meta-requirement algorithm and validating with expert panel in requirements engineering of the algorithm usefulness. Expected result will be that the solution should be able to reverse engineer the meta-requirements of a set of user requirements. By building a repository of meta-requirement, this will enable comparison of meta-requirements of two different system within the same domain and producing a meta-requirement gap analysis. The contribution of this research should be beneficial to industry and researchers.